Analisis Kebutuhan Petugas Pendaftaran Di Rumah Sakit Panti Waluyo Surakarta - nopita - cahyaningrum; Rahaju Muljo Wulandari (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
The role of the registration officer is very important because at the place of registration the patient gets the first service and provides an assessment of the quality of service in the hospital. Therefore, registration officers must be skilled, fast, precise in order to support the completeness of medical record data and provide quality services to patients. Based on the preliminary survey, it is known that there are eleven registration officers divided into three shifts. Problems that occur (1) Registration officers in each work shift consist of two officers serving outpatients, inpatients and the Emergency Room, both general patients and patients with health insurance. (2) Panti Waluyo Surakarta Hospital is the first-level BPJS Referral Hospital, with the stipulation of tiered referral BPJS regulations, the number of patients at Panti Waluyo Surakarta Hospital is increasing. (3) Officers must arrange a break schedule that varies according to the work shift schedule. Quantitative research method with cross sectional approach. The research subjects were eleven registrars and the Head of the Medical Record Installation. The object of research is the workload of Registration Officers. The results of the study are health facilities of the general hospital type with the HRK type of medical record, working time available is 88,800 minutes/year, the standard workload is 403,152, the FTP value is 15.68% and the STP value is 1.19 and the HRK requirement for registration in 2022 is calculated using the ABK method. The case is 15 SDMK. The conclusion of the study is that the need for SDMK in the registration section is 15 SDMK while now there are 11 SDMK so that it requires addition. The author suggests that it is better to add 4 SDMK so that the burden on officers is not excessive and the existing tasks can be completed properly.